95 Exposure to polycyclic aromatic hydrocarbons and sperm DNA integrity of coke oven workers. (11th October 2013) - Jeng, C; Pan,; Lin,
Abstract : The objective of this study was to examine sperm DNA integrity of coke-oven workers in relation to exposure to PAHs from coke processing. A total of 72 human subjects participated in this study: 24 topside-oven workers, 28 side-oven workers, and 20 administrative personnel serving as the high exposure group, low exposure group, and control, respectively. An exposure assessment was conducted to depict the extent of PAH exposure by measuring urinary 1-hydroxypyrene (1-OHP). DNA fragmentation, 8-oxo-7, 8-dihydro-2'-deoxyguanosine (8-oxodGuo), and bulky DNA adducts in sperm DNA were quantified using terminal deoxynucleotidyl transferase-mediated dUTP nick end labelling, liquid chromatography-mass spectrometry/mass spectrometry, and 32P-labelling, respectively. Coke-oven workers had increased levels of DNA fragmentation, 8-oxodGuo, and bulky DNA adducts. However, there was no significant difference in DNA fragmentation levels among the three studied groups ( P = 0.062). The levels of 8-oxodGuo and bulky DNA adducts in the exposed groups were significantly higher than those in the control ( P = 0.048 and 0.032, respectively), while controlling for age, alcohol consumption, and smoking. DNA fragmentation positively correlated with 8-oxodGuo, which suggests that oxidative stress may be linked to DNA breakage. Urinary 1-OHP levels did correlate with 8-oxodGuo levels ( P = 0.036), but not bulky DNA adducts and DNA fragmentation. In summary, exposure to PAHs correlated with oxidative damage and formation of DNA adducts in sperm. Monitoring of sperm DNA integrity is recommended for affected workers as part of any periodic health assessment to determine the impact of occupational toxins on sperm.